Biological Functions of the Secretome of Neisseria meningitidis - Tommassen, Jan; Arenas, Jesús (Frontiers in Cellular and Infection Microbiology, 2017)
Neisseria meningitidis is a Gram-negative bacterial pathogen that normally resides as a commensal in the human nasopharynx but occasionally causes disease with high mortality and morbidity. To interact with its environment, it transports many proteins across the outer membrane to the bacterial cell surface and into the extracellular medium for which it deploys the common and well-characterized autotransporter, two-partner and type I secretion mechanisms, as well as a recently discovered pathway for the surface exposure of lipoproteins. The surface-exposed and secreted proteins serve roles in host-pathogen interactions, including adhesion to host cells and extracellular matrix proteins, evasion of nutritional immunity imposed by iron-binding proteins of the host, prevention of complement activation, neutralization of antimicrobial peptides, degradation of immunoglobulins, and permeabilization of epithelial layers. Furthermore, they have roles in interbacterial interactions, including the formation and dispersal of biofilms and the suppression of the growth of bacteria competing for the same niche. Here, we will review the protein secretion systems of N. meningitidis and focus on the functions of the secreted proteins.